The impact of teacher care on teacher-student relationship: evidence from cross-sectional and longitudinal data - Zhang, Zhen; Wang, Yuxin; Deng, Wenqing; Ma, Xueling; Qi, Chunhui (Frontiers in Psychology, 2025)
Based on a sample of middle school students from the China Education Panel Survey (CEPS) database, this study explores the relationship between parental perceived teacher care and teacher-student relationship and the role of teacher gender in it through cross-sectional and longitudinal studies. Study 1 found that there was a significant positive correlation between teacher gender, parental perceived teacher care and teacher-student relationship. Analysis of simple moderation effects suggests that teacher gender plays a moderating role in the relationship between parental perceived teacher care and teacher-student relationships. Subsequent simple slope analysis indicates that the influence of female teacher care on teacher-student relationship is notably stronger than that of male teacher care. Study 2 Descriptive statistical results indicated that during the seventh and eighth grades of Chinese middle school students, the level of teacher care showed a slight decrease, and teacher-student relationship showed a decreasing trend. Correlational results demonstrated a significant positive correlation between parental perceived teacher care and teacher-student relationship at both time points. Further analysis using cross-lagged models revealed that teacher care significantly positively predicted subsequent teacher-student relationship, and teacher-student relationship significantly positively predicted subsequent teacher care. This bidirectional predictive relationship did not have the moderation of teacher gender. Based on these findings, educators should strengthen the communication and cooperation between parents and teachers, and create a benign educational atmosphere for student interaction in school and family.